Brain BLAQ: Post-hoc thick-section histochemistry for localizing optogenetic constructs in neurons and their distal terminals - David Adam Kupferschmidt; Patrick A Cody; David M Lovinger; Margaret Isabella Davis (Frontiers Media S.A., 2015)
Optogenetic constructs have revolutionized modern neuroscience, but the ability to accurately and efficiently assess their expression in the brain and associate it with prior functional measures remains a challenge. High-resolution imaging of thick, fixed brain sections would make such post-hoc assessment and association possible; however, thick sections often display autofluorescence that limits their compatibility with fluorescence microscopy. We describe and evaluate a method we call Brain BLAQ (Block Lipids and Aldehyde Quench) to rapidly reduce autofluorescence in thick brain sections, enabling efficient axon-level imaging of neurons and their processes in conventional tissue preparations using standard epifluoresence microscopy. Following viral-mediated transduction of optogenetic constructs and fluorescent proteins in mouse cortical pyramidal and dopaminergic neurons, we used BLAQ to assess innervation patterns in the striatum, a region in which autofluorescence often obscures the imaging of fine neural processes. After BLAQ treatment of 260-350 μm-thick brain sections, axons and puncta of labeled afferents were visible throughout the striatum using a standard epifluorescence stereomicroscope. BLAQ histochemistry confirmed that motor cortex (M1) projections preferentially innervated the matrix component of lateral striatum, whereas medial prefrontal cortex projections terminated largely in dorsal striosomes and distinct nucleus accumbens subregions. Ventral tegmental area dopaminergic projections terminated in a similarly heterogeneous pattern within nucleus accumbens and ventral striatum. Using a minimal number of easily manipulated and visualized sections, and microscopes available in most neuroscience laboratories, BLAQ enables simple, high-resolution assessment of virally transduced optogenetic construct expression, and post-hoc association of this expression with molecular markers, physiology and behavior.